ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN NELAYAN TRADISIONAL DI KELURAHAN PASIR PUTIH DISTRIK MANOKWARI TIMUR KABUPATEN MANOKWARI (STUDI KASUS NELAYAN DI WILAYAH PASIRIDO) - Hengky Rumfabe; Rully N. Wurarah; Sisilia Maria Parinusa (Jurnal Ilmu Ekonomi, 2021)
This study aims to determine the effect of demand, fish prices and production costs on the income of traditional fishermen in the Pasirido area, East Manokwari District before and after the COVID-19 pandemic and whether there is a difference in the income of traditional fishermen both before and after the pandemic. The type of this research is quantitative descriptive with the number of samples used in this study are 45 traditional fishermen. According to analysis result, it is known that both before and after pandemic COVID -19 consumption, selling price have a positive and significant effects to the fishermen’s income on the other hand cost production has a negative and significant effect. Furthermore, before the pandemic it was known that the average income of fishermen was IDR 2,392,422.22 and after the pandemic the average income of fishermen was IDR 2,174,866.67. In addition, the most dominant variable that affects the income level of fishermen both before and after the pandemic is the variable of consumption or community demand